Herbicide Programs for Annual Bluegrass (Poa annua L.) Control in Nebraska. Issue 1 (10th March 2017) - Reicher, Zachary; Sousek, Matt; Giese, Matt
Abstract : Core Ideas: Research done on annual bluegrass (ABG) control in other areas of the US are likely applicable to Nebraska. However, extreme weather can dramatically affect short‐term annual bluegrass cover and emphasize the need for long‐term control studies. Three fall POST applications of mesotrione plus prodiamine applied preemergence in August and/or November were effective for ABG control in Kentucky bluegrass fairways. Replacing mesotrione with ethofumesate was also effective when combined with prodiamine in August and November. June applications of bispyribac‐sodium at 4 oz/ac was highly effective for controlling ABG in creeping bentgrass fairways, and adding two more fall applications at the same rate improved control slightly, but there was no benefit to raising the rate to 6 oz/ac. Annual bluegrass ( Poa annua L.) (ABG) is common in golf courses, and its control has been thoroughly researched in cool‐season turf east of the Mississippi River in the United States. However, ABG response to herbicides varies widely among environments and/or biotypes, and little ABG control research has been done in the northern Great Plains. Therefore, our objective was to validate ABG herbicide control systems in golf course fairways of Kentucky bluegrass ( Poa pratensis L.) (KBG) or creeping bentgrass ( Agrostis stolonifera L.) (CBG) in Nebraska. Preemergence (PRE) treatments of prodiamine or mesotrione were applied in late summer over 3 yr with or without fall postemergence (POST) treatments of mesotrione or ethofumesate for ABG control in a low‐mow KBG fairway. We also evaluated rate and frequency of bispyribac‐sodium applications with or without a late summer–applied PRE (dithiopyr) in early September for ABG control over 3 yr in a CBG fairway. Our research indicates that ABG control work done in other areas are likely applicable to Nebraska. Three fall POST applications of mesotrione plus prodiamine applied as a PRE in August and/or November was effective for ABG control in KBG fairways. Replacing mesotrione with ethofumesate was also effective when combined with prodiamine in August and November. June applications of bispyribac‐sodium at 4 oz/ac were highly effective for controlling ABG in CBG fairways, and adding two more fall applications at the same rate improved control slightly, but there was no benefit to raising the rate to 6 oz/ac. Lastly, extreme weather in one summer and one winter dramatically affected short‐term ABG cover and emphasized the need for long‐term control studies in areas with dramatic weather cycles.